Enhancing the stability of dimethyl ether carbonylation over Fe-doped MOR zeolites with tunable 8-MR acidity. (20th July 2022) - Zhang, Li-Yun; Feng, Xiao-Bo; He, Zi-Meng; Chen, Feng; Su, Chang; Zhao, Xiao-Yan; Cao, Jing-Pei; He, Yu-Rong
Graphical abstract: Highlights: Fe-doped MOR zeolites were synthesized using oxalic acid as the complexing reagent. Fe atoms preferentially form Fe(OH)Si groups at the 8-MR rather than at the 12-MR. Fe-doped MOR embrace gradient concentration of B8‑MR and well-maintained B12-MR . The decreasing B8-MR grants Fe-doped MOR good stability and high MA selectivity. Abstract: Dimethyl ether (DME) carbonylation to methyl acetate (MA) paves a desirable way for producing ethanol from syngas. However, designing highly durable catalysts for it is still extremely challenging. In the work, we designed a series of Fe-doped MOR zeolites using oxalic acid as the complexing reagent by a template-free method. It is found that the complexed iron (III) preferentially locates at the T3 position of the eight-membered ring (8-MR). Over these Fe-doped MOR zeolites, the stability of DME carbonylation can be significantly enhanced. Contradictory to the conventional understanding of B8-MR, we suggest that the decrease in the B8-MR leads to relatively good stability, long introduce period, high MA selectivity and high MA production efficiency of B8-MR . The work not only provides a new strategy for regulating the acid distribution of HMOR, but also offers a new understanding in the role of the B8-MR in the carbonylation of DME.